2015
DOI: 10.1891/1052-3073.26.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Savings Goals and Saving Behavior From a Perspective of Maslow's Hierarchy of Needs

Abstract: The purpose of this study was to examine associations between saving goals and saving behavior from a perspective of Maslow's Hierarchy. Using 1998-2007 Surveys of Consumer Finance datasets, we analyzed responses given to an open ended saving reason question, and categorized responses into six saving goals. The retirement/security goal was the most frequently mentioned, and the self-actualization goal was the least frequently mentioned. We tested two models to ascertain whether the order of response differed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 53 publications
4
64
0
4
Order By: Relevance
“…Households who believed they could obtain emergency funds from friends or relatives were more likely to save than were similar households without that belief. Some of the results are contrary to the life cycle hypothesis, but there is similar empirical evidence in the literature, for example, future income (Rha et al., ; Yuh & Hanna, ), health status (Fisher & Montalto, ; Heckman & Hanna, ; Lee & Hanna, ), and having better access to social support (Yuh & Hanna, ).…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Households who believed they could obtain emergency funds from friends or relatives were more likely to save than were similar households without that belief. Some of the results are contrary to the life cycle hypothesis, but there is similar empirical evidence in the literature, for example, future income (Rha et al., ; Yuh & Hanna, ), health status (Fisher & Montalto, ; Heckman & Hanna, ; Lee & Hanna, ), and having better access to social support (Yuh & Hanna, ).…”
Section: Resultsmentioning
confidence: 77%
“…Some have used changes in net worth (Browning & Lusardi, ; Chang, ; Kennickell, ; Lewis, ), or the residual between income and consumption (Bae, Hanna, & Lindamood, ; Browning & Lusardi, ; Jayathirtha & Fox, ), while others have used the respondent's assessment of whether or not household spending was less than income (Kennickell, ; Lee & Hanna, ; Rha et al., ; Yuh & Hanna, ). Recently, researchers have found that the measure based on respondents’ self‐reports of whether spending was more or less than income was useful in studies focused on behavioral factors related to household saving (Fisher, ; Fisher & Montalto, ; Heckman & Hanna, ; Kennickell, ; Lee & Hanna, ; Rha et al., ; Yuh & Hanna, ). This measure of saving is used in Federal Reserve Board reports (Bricker et al., ).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Goal setting is often defined as a commitment to control time-inconsistent preferences and processes to enhance the productivity and satisfaction of goal holders (G omez-Miñambres, 2012). Examples include improved learning, job performance, mental health, and saving decisions (Lee & Hanna, 2015). However, the intention to set a goal by itself does not guarantee successful goal achievement because there might be a discrepancy between goal setting and implementation (Soman & Zhao, 2011).…”
Section: Propensity To Planmentioning
confidence: 99%
“…Fisher, Hayhoe, dan Lown (2015) mendefinisikan perilaku menabung sebagai kecenderungan untuk menyimpan dana dengan melihat cara untuk menabung, frekuensi menabung, dan jumlah dana yang akan ditabung secara kontinyu. Faktor-faktor yang mempengaruhi perilaku menabung tersebut telah banyak diteliti, namun pada sektor perbankan (Abrahamse & Steg, 2009;Lee & Hanna, 2015) dengan menggunakan Theory of Planned Behavior (TPB) yang diperkenalkan Ajzen (1991). Teori ini menjelaskan perilaku seseorang dipengaruhi oleh minat untuk berperilaku, sedangkan minat sendiri ditentukan oleh sikap, norma subjektif, dan kontrol perilaku persepsian.…”
Section: Pendahuluanunclassified